Unpacking the impact of gratitude on unethical behavior - Oh, Junho (Deviant behavior, 2024)
Understanding and preventing unethical behavior is essential for social welfare. Prior research has shown that emotional processes have consequential effects on such behavior. The current work aims to unravel the mixed findings relating positive emotion to unethical behavior by suggesting that feeling gratitude may differentially influence one’s ethicality through three distinct pathways: cognitive (moral disengagement), motivational (greed), and relational (felt-security). Through our propositions, we advance a conceptual model for investigating the relationships among general positive emotion, gratitude, and unethical behavior, to gain clarity on these important connections. More broadly, researchers could use our model to illuminate a range of pathways linking gratitude and unethical behavior.